Early life famine exposure to the Great Chinese Famine in 1959–1961 and subsequent pregnancy loss: a population‐based study. (10th September 2019) - Zhang, H; Qu, X; Wang, H; Tang, K
Abstract : Objective: To explore the relation between famine exposure in early life and subsequent pregnancy loss, including stillbirth, and spontaneous abortion in adulthood. Design: A population‐based, partly ecological study. Setting and population: Individual data of 58 601 females born around the time of the Great Chinese Famine in 1959–1961. Methods: Associations between the famine exposure in early life and pregnancy loss (stillbirth and spontaneous abortion) in adulthood were analysed using negative binomial regression, with the non‐exposure group as reference, adjusting for region, highest education, monthly income, alcohol consumption, tobacco use, body mass index in 25‐year‐olds and metabolic equivalent. Further analyses were stratified by rural versus urban region. Main outcome measures: Continuous variables of times of stillbirths and spontaneous abortions were used according to the individual self‐reported reproductive history. Results: No association was found between famine exposure and spontaneous abortion. In contrast, females experiencing the famine during their prenatal period (incidence rate ratio = 1.15, 95% CI 1.00–1.33) or infant period (incidence rate ratio = 1.27, 95% CI 1.12–1.44) were more likely to report stillbirth in later adult life. Such an association appeared stronger in women living in rural regions. Conclusions: Early life exposure of famine was associated with an increased risk of stillbirth but not spontaneous abortion in adulthood. The strength of such an association appeared stronger in rural areas. Given the high potential for unmeasured confounding, these associations must be interpreted with caution. Regarding the potential implication that undernutrition in the fetal period is related to reproductive outcome in adulthood, fetal nutritional supply may play an important role in human reproduction. Tweetable abstract: Exposure to famine in early life was associated with increased pregnancy loss in adulthood. Tweetable abstract: Exposure to famine in early life was associated with increased pregnancy loss in adulthood.